Pure vegetable oil for energy and transport. (5th May 2009) - Chiaramonti, David; Prussi, Matteo
Pure Vegetable Oil (PVO) is a 100% renewable fuel obtained from oil crops. PVO can be produced in a distributed manner in rural areas and commercial technologies almost exist for energy and transports, making possible to develop small scale chains, suitable for both industrialised as well as developing countries. The aim of the research work is to investigate over a three-year period the complete PVO chain under Italian conditions, i.e., crop selection, plantation and harvesting, seed drying and storage, oil extraction, cake (coproduct) valorisation and PVO use in small generators, cogenerators, micro gas turbines and greenhouse/school heating systems, supporting experimental work with environmental and socio-economic studies. The aim of the present paper is to present the results obtained at the end of the first year, as regards oil production in both cold decentralised systems and industrial systems, as well testing of the oil in a modified tractor. The PVO produced in the cold press met the current DIN specifications for PVO in engines and the performance of the tractor was very similar to standard tractors. [Received: January 29, 2009; Accepted: March 4, 2009]